Penerapan Standar Akuntansi Pemerintahan Dalam Penyusunan Laporan Keuangan Pada Pemerintah Daerah Kabupaten Labuhanbatu Provinsi Sumatera Utara - Marja Sinurat; Rizqi Sukma Sari Putri; Womsiter Sinaga; Ayu Widowati Johannes (Fakultas Manajemen Pemerintahan, Institut Pemerintahan Dalam Negeri, 2023)
ABSTRACT The application of good accrual-based government accounting standards (SAP) will influence the opinion given by the Audit Board (BPK) on regional financial management. The purpose of the study is to determine how the implementation, obstacles that occur and efforts to overcome obstacles in Government Accounting Standards in the preparation of Local Government Financial Statements (LKPD) of Labuhanbatu Regency, North Sumatra Province. The study used descriptive qualitative methods with an inductive approach, primary and secondary data sources with data collection through documentation, observation and interviews which were then analyzed with the miles and huberman model. The implementation of the preparation of local government financial statements of Labuhanbatu Regency has implemented accrual-based government accounting standards. There are still obstacles that occur in the form of the implementation of standard operating procedures and lack of competence and the amount of resources of the financial statement preparation apparatus. Efforts are made by increasing the competence and number of apparatus resources based on accounting education background and the application of standard operating procedures. The implementation of SAP in Labuhanbatu Regency still has obstacles in the form of apparatus resources and standard operating procedures. BPKAD seeks to overcome obstacles that occur by increasing the competence and amount of apparatus resources as well as the implementation of SAP standard operating procedures. Keywords: SAP Implementation, Accrual Basis, and Financial Statements ABSTRAK Penerapan Standar akuntansi pemerintahan (SAP) berbasis akrual yang baik akan mempengaruhi opini yang diberikan oleh Badan Pemeriksa Keuangan (BPK) terhadap pengelolaan keuangan Daerah. Tujuan dari penelitian untuk mengetahui bagaimana penerapan, hambatan yang terjadi dan upaya dalam mengatasi hambatan dalam Standar Akuntansi Pemerintah dalam penyusunan Laporan Keuangan Pemerintah Daerah (LKPD) Kabupaten Labuhanbatu Provinsi Sumatera Utara. Penelitian menggunakan metode kualitatif deskriptif dengan pendekatan induktif, sumber data primer dan sekunder dengan pengumpulan data melalui dokumentasi, observasi dan wawancara yang kemudian dilakukan analisis dengan model Miles and Huberman. Pelaksanaan penyusunan LKPD Kabupaten Labuhanbatu telah menerapkan SAP berbasis akrual. Masih terdapat hambatan yang terjadi berupa penerapan standar operasional prosedur serta kurangnya kompetensi dan jumlah sumber daya aparatur penyusun laporan keuangan. Upaya yang dilakukan dengan peningkatan kompetensi dan jumlah sumber daya aparatur berdasarkan latar belakang pendidikan akuntansi dan penerapan standar operasional prosedur. Penerapan SAP di Kabupaten Labuhanbatu masih terdapat hambatan berupa sumber daya aparatur dan standar operasional prosedur. BPKAD berupaya mengatasi hambatan yang terjadi dengan meningkatkan kompetensi dan jumlah sumber daya aparatur serta penerapan standar operasional prosedur SAP. Kata kunci: Penerapan SAP, Basis Akrual, dan Laporan Keuangan.